Developing geometry pop-up book using universal design for learning approach for students with intellectual disabilities in Yogyakarta - Anisa Nurbaiti; Nisrina Diva Adhani; Nandini Rohmi; Heru Sukoco (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
Education is a universal right for all individuals, including Children with intellectual disabilities (ID). Therefore, the study aimed to develop a valid, practical, and effective Pop-up Book using the Universal Design for Learning (UDL) approach to geometry material for students with intellectual disabilities in one of the Schools for Students with Special Needs in Yogyakarta. It used a developmental research method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The population was all students with intellectual disabilities in one of the State Schools for Students with Special Needs in Yogyakarta. The sample was 10 students, selected using the purposive sampling technique. The study concluded that the Pop-up Book was valid. Based on the limited test, the results of the ten representative ability test questions were also valid and reliable. Moreover, the pop-up book developed was practical from the student's perspective. The average pre-test and post-test results effectively improved the learning outcomes of students with intellectual disabilities in geometry material. Thus, the Pop-up Book Geometry using the Universal Design for Learning approach was valid, practical, and effective.